Spatiotemporal analysis of childhood cancers in Iran (2005–2013). (August 2022) - Saffar, Azam; Azizmohammad Looha, Mehdi; Khodakarim, Soheila; Akbari, Mohammad Esmaeil; Mehrabi, Yadollah
Abstract: Background: Childhood cancers are among the leading causes of child mortality worldwide. We aimed to analyze the spatiotemporal incidence patterns of five common cancer types in Iran. Material and methods: A total of 17155 incident malignant 0-14 years old cases during 2005-2013 recorded by the Iran National Cancer Registry were included. An adaptive spatiotemporal smoothing model was applied to explore spatiotemporal variations of the age-standardized incidence rate (ASIR). Results: The highest overall ASIR was estimated at 137.9 per million person-years in 2011-2013. Most of the five common cancers had an increasing trend in most provinces for both males and females during this time. Conclusion: Increasing ASIR and risk of cancers were observed during the study period, which follows the trend of childhood cancers incidence worldwide. The health system should take this rise as a serious alarm and provide appropriate prevention plans.